Expression of Helicobacter pylori urease genes in Escherichia coli grown under nitrogen-limiting conditions. - Cussac, V (1992)
Helicobacter pylori produces a potent urease that is believed to play a role in the pathogenesis of gastroduodenal diseases. Four genes (ureA, ureB, ureC, and ureD) were previously shown to be able to achieve a urease-positive phenotype when introduced into Campylobacter jejuni, whereas Escherichia coli cells harboring these genes did not express urease activity (A. Labigne, V. Cussac, and P. Courcoux, J. Bacteriol. 173:1920-1931, 1991). Results that demonstrate that H. pylori urease genes could be expressed in E. coli are presented in this article. This expression was found to be dependent on the presence of accessory urease genes hitherto undescribed. Subcloning of the recombinant cosmid pILL585, followed by restriction analyses, resulted in the cloning of an 11.2-kb fragment (pILL753) which allowed the detection of urease activity (0.83 +/- 0.39 mumol of urea hydrolyzed per min/mg of protein) in E. coli cells grown under nitrogen-limiting conditions. Transposon mutagenesis of pILL753 with mini-Tn3-Km permitted the identification of a 3.3-kb DNA region that, in addition to the 4.2-kb region previously identified, was essential for urease activity in E. coli. Sequencing of the 3.3-kb DNA fragment revealed the presence of five open reading frames encoding polypeptides with predicted molecular weights of 20,701 (UreE), 28,530 (UreF), 21,744 (UreG), 29,650 (UreH), and 19,819 (UreI). Of the nine urease genes identified, ureA, ureB, ureF, ureG, and ureH were shown to be required for urease expression in E. coli, as mutations in each of these genes led to negative phenotypes. The ureC, ureD, and ureI genes are not essential for urease expression in E. coli, although they belong to the urease gene cluster. The predicted UreE and UreG polypeptides exhibit some degree of similarity with the respective polypeptides encoded by the accessory genes of the Klebsiella aerogenes urease operon (33 and 92% similarity, respectively, taking into account conservative amino acid changes), whereas this homology was restricted to a domain of the UreF polypeptide (44% similarity for the last 73 amino acids of the K. aerogenes UreF polypeptide). With the exception of the two UreA and UreB structural polypeptides of the enzyme, no role can as yet be assigned to the nine proteins encoded by the H. pylori urease gene cluster.